The Function of Content Mastery Services in Fostering Students' Interest in Learning in Senior High School - Susmita Br. Siregar, Tiya Modi; Mahidin, Mahidin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this research is to find out how the content mastery service of SMA Muhammadiyah 09 Kualuh Hulu helps students become more interested in learning. Students' study habits are developed due to this learning, and if they already have good study habits, they must be maintained. This research uses qualitative methods with a Case Study approach. The sample of this study consisted of 36 students of SMA Muhammadiyah 09 Kualuh Hulu. The data collection instruments of this research are in-depth interviews and observation. The data analysis technique used is data reduction; data reduction is a thinking process that requires a depth of insight; after reducing the data, the data is described, or what is often called data presentation; after the data is processed properly, the researcher concludes. The data validity test technique in this study uses triangulation by asking the same thing with different sources. The results showed that the content mastery services provided positively impacted students' interest in learning. This result is supported by the assessment given to students in the written test group every time they complete the material mastery activities and observed by the observation that students often lose focus in learning and often do not write school notes when learning takes place and after the implementation of student access to content mastery services it is increasingly clear that the increase in learning interest is growing towards students.